Pengaruh Harga, Promosi, Kualitas Pelayanan, Dan Citra Merek Terhadap Keputusan Pembelian Pada Pengguna Shopee Di Bandung - Indah Fransiska; Putu Nina Madiawati (Jurnal Sekretaris dan Administrasi Bisnis, 2022)
In March 2020, the covid-19 virus entered Indonesia, which led to the establishment of restrictions on outdoor activities and resulted in an increase in the use of e-commerce platforms. Shopee is one of the e-commerce that has increased. Therefore, the purpose of this research is to see how shopee users in Bandung perception of Price, Promotion, Quality of Service, Brand Image, and Purchase Decision and also to see the influence of Price, Promotion, Quality of Service, Brand Image to Purchase Decisions on Shopee Users in Bandung in a Partial and Simultaneous. Data analysis uses multiple linear regression analysis, with descriptive quantitative methods. The number of samples used as many as 100 shopee users domiciled in Bandung with non-probability sampling method with snowball sampling type. The results of the study found that partially the price and quality of service had no significant effect on purchasing decisions, while on promotion and brand image had a significant effect on purchasing decisions. While simultaneously it was obtained that their price, promotion, quality of service, and image significantly influenced the purchase decision by 54.3% and the remaining 45.7% was influenced by other variables not studied in this study